The use of hyperuricemia herbs at “Hortus Medicus” herbal medicine clinic Tawangmangu - Danang Ardiyanto; Agus Triyono; Ulfatun Nisa; Ulfa Fitriani; Peristiwan RW Astana; Fajar Novianto; Zuraida Zulkarnain (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Hyperuricemia has become a health problems in Indonesia lately. The use of traditional medicine, especially herbs, has been used in the treatment of hyperuricemia. Hortus Medicus Herbal Medicine Clinic Tawangmangu has several herbal formulas that are applied in the care of hyperuricemia patients.Objective: This study aims to determine the description of the mostly used medicinal plants for hyperuricemia and the percentage of efficacy of hyperuricemia therapy using medicinal plant. Methods: This study was a retrospective cross-sectional study using purposive sampling. The total sample was 120 medical records and prescriptions for hyperuricemia patients at Hortus Medicus clinic for the period July-December 2020. Results: There were 3 hyperuricemia herbs formulas used in Hortus Medicus. Based on the calculation of the doctor's prescription for hyperuricemia, the first herbal formula consisting of secang (Caesalpinia sappan) bark, tempuyung (Sonchus arvensis) herb, kepel (Stelechocarpus burahol) leaf was prescribed as many as 72 prescriptions (60%). The second herbal formula consisting of cabe jawa (Piper retrofactum), daun sendok (Plantago mayor) leaves, celery (Apium graveolens) herbs with 36 prescriptions (30%), and the third herbal formula consisting of rumput bolong (Equisetum debille) herb, temulawak (Curcuma xanthorizza), turmeric (Curcuma domestica) with 12 prescriptions (10%). The therapeutic efficacy of herbal formula 1st, 2nd and 3rd were 80%; 60%; 50%. There was no significant relationship between sex and the outcome of hyperuricemia therapy (p= 0.804).Conclusion: Among three hyperuricemia herbal formulas used in Hortus Medicus, the 1st formula was mostly used. The percentage of therapeutic efficacy was also higher compared to the other two formulas.